(untitled) (Research, Society and Development, 2021)
This paper is about a hydrological and hydraulic modeling at the urban drainage system in the Administrative Region of Riacho Fundo I in the Federal District from the rainfall and runoff data monitored in 21 events between 2018 and 2019 with the SWMM model. The objective of the research was to analyze the calibration of the runoff model for the study area in order to validate the use of the tool in the management of urban drainage. The PCSWMM program was used, which has the SRTC automatic calibrator, which allows the variation of the parameters through the analysis of uncertainties. The simulation was carried out continuously, with the analysis of each event individually, with the event on 03/12/19 having the best objective functions when calibrated (ISE = 4.64, NSE = 0.851, R² = 0.865, SEE = 0.466, LSE = 17.4, RMSE = 3.28). With the calibrated model, 20 events were validated and although 40% of them presented negative NSE due to overestimation of Qpico, the model was considered satisfactory, considering that this problem can be attributed to the difficulty of measuring large flows. Therefore, the accomplishment in the calibration and validation of the proposed hydrological and hydraulic model for the region was achieved. These tools are important for the management of rainwater, including the dimensioning of systems with compensatory measures.